Infinite nested radicals

Algebra Level 4

E = z + z z + z . . . \mathscr{E} = \sqrt{z+ \sqrt{z - \sqrt{z+ \sqrt{z-...}}}} What's the lowest non-negative value not equal to 0 0 nor 1 1 for z z , which makes E \mathscr{E} a natural number?


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Krishna Sharma
Oct 13, 2014

y = 1 + 4 z 3 2 \displaystyle y = \frac{1 + \sqrt{4z - 3}}{2}

4z - 3 should be perfect square and the least possible value of z is 3 \boxed {3} When y is natural number

Excellent job, Krishna! I'm glad that you didn't involve quartic equation.

Hobart Pao - 6 years, 8 months ago

Log in to reply

And how is this an "excellent job"? The solution does not even explain where the first expression even came from.

Is this why kids can't learn math? Apparently teachers employ similar expedients in classrooms.

John M. - 6 years, 7 months ago

Log in to reply

Sorry john! I have generalised these type of equations

I can explain

y = z + z \displaystyle y = \sqrt{z + \sqrt{z - \ldots}}

Let

k = z z + \displaystyle k = \sqrt{z - \sqrt{z + \ldots }}

Squaring both equation

y 2 = z + k \displaystyle y^{2} = z + k

k 2 = z y \displaystyle k^{2} = z - y

Eliminating 'k' from the equation we will get quadratic of 'z' now you can solve the equation(sorry for that I am short on time) and rearrange in terms of 'y' you will get the above equation.

Krishna Sharma - 6 years, 7 months ago

Log in to reply

@Krishna Sharma Much better.

Thanks!

John M. - 6 years, 7 months ago

@Krishna Sharma Exactly! Much similar to Ostrich's Nested Radical

Satvik Golechha - 6 years, 6 months ago

Excellent job meaning solving the problem.

Hobart Pao - 6 years, 7 months ago

@krishna sharma........... how did u write the first equation ........please explain

Vibhooti Singh - 6 years, 8 months ago
Prakhar Gupta
Jan 29, 2015

The given equation may be rewritten as:- z + z y = y \sqrt{z+\sqrt{z-y}}=y Squaring both sides:- z + z y = y 2 \implies z+\sqrt{z-y}=y^{2} z y = y 2 z \implies \sqrt{z-y} = y^{2}-z Squaring both sides again:- z y = y 4 2 y 2 z + z 2 \implies z-y = y^{4}-2y^{2}z+z^{2} Rearranging the above terms:- z 2 z ( 1 + 2 y 2 ) + y + y 4 = 0 \implies z^{2}-z(1+2y^{2}) + y + y^{4} = 0 Solving by quadratic formula:- z = 1 + 2 y 2 ± 1 + 4 y 2 + 4 y 4 4 ( y + y 4 ) 2 \implies z=\dfrac{1+2y^{2}\pm \sqrt{1+4y^{2}+4y^{4}-4(y+y^{4})}}{2} Solving It we get:- z = y + y 2 o r z = y 2 y + 1 z=y+y^{2} or z=y^{2} - y +1 We have to find the values of z for which y is a natural number.

Put y = 0 y =0 in both the above equations, we get a z = 0 z=0 and 1 1 . Which are not allowed.

Put y = 1 y=1 in both the above equations, we get z = 2 z=2 and 1 1 .

If we put z = 2 z=2 in the given equation, we will find inconsistency. So we will neglect it.

Put z = 2 z=2 in both the equations. We get z = 6 , 3 z=6, 3 .

Put z = 3 z=3 in the given equation. We get the equations are consistent.

Hence z = 3 z=3 is the smallest values for which y y is a natural number.

Lucas Tell Marchi
Jan 10, 2015

First of all, observe that

y 2 = x + x y y 4 2 y 2 x + y + x 2 x = 0 y^{2} = x + \sqrt{x-y} \;\;\; \Rightarrow \;\;\; y^{4} - 2y^{2}x + y + x^{2} - x = 0

Now, a little theorem says that the only possible rational irreductible roots a b \frac{a}{b} of a polynomial equation with integer coefficients c n x n + + c 1 x + c 0 = 0 c_{n}x^{n} + \cdots + c_{1}x + c_{0} = 0 are those in which a a divides c 0 c_{0} and b b divides c n c_{n} .

Therefore, for our polynomial in y y , the only possible roots are y = x y = x and y = x 1 y = x - 1 .

Testing for y = x y = x gives us x 4 2 x 3 + x 2 = x 2 ( x 2 2 x + 1 ) = 0 x^{4} - 2x^{3} + x^{2} = x^{2}(x^{2}-2x+1) = 0 with x 0 x \neq 0 which has the only root x = 1 x = 1 . But this is not the answer, according to the problem. Therefore, y x y \neq x .

Testing for y = x 1 y = x - 1 we'll get y 2 = x + x y x ( x 3 ) = 0 y^{2} = x + \sqrt{x-y} \;\;\; \Rightarrow \;\;\; x(x-3) = 0 with x 0 x \neq 0 . Therefore x = 3 x = 3 . Then

x = 3 x = 3

Christian Daang
Nov 16, 2014

Since y = √(z+√(z-√(z+√(z-√(z+⋯)) ) ) ) = √(z+√(z-y)) ,

y = √(z+√(z-y))

y^2 = z+ √(z-y)

y^2 - z = √(z-y)

Since √(z-y) should be a natural #, then, z-y >/= 0 ---> z >/= y ---->Least posible value of z: y+1. then,

y^2 = y+1+1 or y^2 = y+1-1

y^2 - y - 2 = 0 or y^2 - y = 0

y = {2,-1} or y = {0,1}

In y = {2,-1}, reject -1 since it's not a natural #. So, y = 2 is acceptable. then, z = 3

in y = {0,1}, reject 0 since it's not a natural #. so, y = 1 is acceptable. and as a result, z = 2

But, if you will recheck or substitute: (y,z) = (1,2) in y^2 = z+ √(z-y) , It will not satisfy the equation, only (y,z) = (2,3). So therefore, The smallest possible value of z is 3.

Michael Mendrin
Nov 1, 2014

You should explain why the answer isn't 1.

You know, if you read the question, maybe you'll figure that out.

Hobart Pao - 6 years, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...